Bear's day out - Rosen, Michael, 1946- (Bloomsbury Children's Books : Distributed to the trade by Holtzbrinck Publishers, 2007)
When Bear decides to visit the city, he becomes overwhelmed with all the noise, but luckily some helpful children guide him on his way home again.